El fotoensayo como herramienta de fortalecimiento en la conciencia social. Un análisis de caso Resistance 883 - Molina Herrera, Melissa Lizbeth (Machala, 2020)
The following research seeks to analyze the photo essay as a tool for strengthening social consciousness. A case study "Resistance 883", with this theme seeks to identify the qualities and characteristics of photoessays to inspire social consciousness, focused on values and people's actions. The research meets the following general objective analyze the photo essay as a tool for strengthening social consciousness, identified the methodology of research has a qualitative approach with the application of two research techniques, including the interview that was applied to three specialists in photojournalism, they indicate their work with photojournalism and photoessay, and as a second technique is the case analysis which was implemented to photoessay Resistance 883, in two categories, the first consists of the application of a workshop for university students of communication, jurisprudence and psychology. The second is dedicated to the condensed analysis of the author. to validate whether the photo essay is a tool that strengthens awareness in society. In the conclusions it is highlighted that photoessays are a medium which serve as a tool that generates and strengthens social awareness due to the presence of sensitive content which, according to the results, the use of communicational products generates that people reason in dependence on some act that is harmful to society. In general, it is concluded that photo-essays favour storytelling through a series of photos.
La siguiente investigación busca analizar el fotoensayo como herramienta de fortalecimiento en la conciencia social. Un análisis de caso “Resistance 883. Con esta temática se busca identificar las cualidades y características del fotoensayo para inspirar la conciencia social, enfocada en valores y el accionar de las personas. La investigación cumple con el siguiente objetivo general analizar el fotoensayo como herramienta para el fortalecimiento de la conciencia social, se identificó la metodología de la investigación que tiene un enfoque cualitativo con la aplicación de dos técnicas de investigación, entre ellas la entrevista que se aplicó a tres especialistas en el fotoperiodismo, ellos indican su trabajo realizado con el fotoperiodismo y el fotoensayo, y como segunda técnica se encuentra el análisis de caso el cual fue implementado al fotoensayo Resistance 883, en dos categorías, la primera consta de la aplicación de un taller para estudiantes universitarios de comunicación, jurisprudencia y psicología. La segunda que va dedicada al análisis condensado de la autora para validar si el fotoensayo es una herramienta que fortalece la conciencia en la sociedad. En las conclusiones se destaca que el fotoensayo es un medio el cual sirve como una herramienta que genera y fortalece la conciencia social por la presencia de contenido sensible que según los resultado provoca por ello el uso de productos comunicacionales generan que las personas razonen en dependencia a algún acto que sea perjudicial para la sociedad. En general se concluye que el fotoensayo favorece al conteo de historias mediante una serie de fotos.
Keywords: FOTOENSAYO; FOTOGRAFIA; CONCIENCIA SOCIAL